How Entrepreneurial Teams' Heterogeneity and Learning Experiences Affect Business Performance through Self-Efficacy - Aprilia Amanda, Indah; Tuti, Meylani (School of Business, IPB University (SB-IPB), 2024)
This study aims to ascertain how entrepreneurial learning experiences and entrepreneurial team heterogeneity affect self-efficacy and, consequently, company performance. Members of the Jakpreneur community from the East and North Jakarta metropolitan areas made up the study's demographic. Accidental sampling was the method employed, with 237 respondents who volunteered to complete the author's questionnaire. Using SmartPLS software, a structural equation model is used for data analysis. The findings of the study demonstrate a direct relationship between self-efficacy and company performance entrepreneurial learning experiences and entrepreneurial team heterogeneity. Subsequently, self-efficacy can serve as a moderator to demonstrate the indirect impact of entrepreneurial team heterogeneity and entrepreneurial learning experience on business performance. Learning experiences and diversity in the team both boost self-confidence, which in turn creates a positive feedback loop between motivation and company performance.